Ultimatum Games, Easy Money is Generosity? A Violation of Rational Homo Economicus - Kiky, Andreas (Integrated Journal of Business and Economics (IJBE), 2025)
This study investigates fairness behaviour in the Ultimatum Game by examining proposer-to-responder offer ratios in same-gender dyads within the Indonesian cultural context. One hundred twelve undergraduate students (56 pairs) participated in a one-shot game involving a Rp 10,000 endowment. The research aims to determine whether same-gender pairs, specifically male–male and female–female, deviate from classical rationality models and align with normative fairness expectations. Female proposers offered higher and more consistent amounts than male proposers. The Wilcoxon Signed-Rank Test showed that offers did not significantly differ from an equal-split benchmark (50%) but were significantly higher than the commonly reported 40% average. Although the Mann–Whitney U test did not reach conventional significance (p = 0.053), a marginal trend suggested greater fairness in female–female pairs. These findings indicate that fairness decisions are shaped by gender dynamics and cultural norms emphasising social harmony and equality. The study contributes to behavioural economics by highlighting the role of gender and context in shaping deviations from self-interested behaviour. Limitations include social familiarity between participants and the use of externally provided money. Future research should explore stranger pairings and link proposer resources to personal or charitable outcomes to further test fairness motivations.